1) 0,4(х - 3) = 0,5(4 + х) - 2,5 2) 0,5(х - 3) = 0,6(4 + х) - 2,6
0,4х - 1,2 = 2 + 0,5х - 2,5 0,5х - 1,5 = 2,4 + 0,6х - 2,6
0,4х - 0,5х = 2 - 2,5 + 1,2 0,5х - 0,6х = 2,4 - 2,6 + 1,5
- 0,1х = 0,7 - 0,1х = 1,3
х = 0,7 : (- 0,1) х = 1,3 : (- 0,1)
х = - 7 х = - 13
3) 0,3(5х - 7) = 3(0,2х + 3,2) 4) 0,9(4у - 2) = 0,5(3у - 4) + 4,4
1,5х - 2,1 = 0,6х + 9,6 3,6у - 1,8 = 1,5у - 2 + 4,4
1,5х - 0,6х = 9,6 + 2,1 3,6у - 1,5у = - 2 + 4,4 + 1,8
0,9х = 11,7 2,1у = 4,2
х = 11,7 : 0,9 у = 4,2 : 2,1
х = 13 у = 2
5) 2(0,6х + 1,85) - 0,7 = 1,3х 6) 0,2(5у - 2) = 0,3(2у - 1) - 0,9
1,2х + 3,7 - 0,7 = 1,3х 1у - 0,4 = 0,6у - 0,3 - 0,9
1,2х - 1,3х = - 3,7 + 0,7 1у - 0,6у = - 0,3 - 0,9 + 0,4
- 0,1х = - 3 0,4у = - 0,8
х = - 3 : (- 0,1) у = - 0,8 : 0,4
х = 30 у = - 2
1) 0,4(х - 3) = 0,5(4 + х) - 2,5 2) 0,5(х - 3) = 0,6(4 + х) - 2,6
0,4х - 1,2 = 2 + 0,5х - 2,5 0,5х - 1,5 = 2,4 + 0,6х - 2,6
0,4х - 0,5х = 2 - 2,5 + 1,2 0,5х - 0,6х = 2,4 - 2,6 + 1,5
- 0,1х = 0,7 - 0,1х = 1,3
х = 0,7 : (- 0,1) х = 1,3 : (- 0,1)
х = - 7 х = - 13
3) 0,3(5х - 7) = 3(0,2х + 3,2) 4) 0,9(4у - 2) = 0,5(3у - 4) + 4,4
1,5х - 2,1 = 0,6х + 9,6 3,6у - 1,8 = 1,5у - 2 + 4,4
1,5х - 0,6х = 9,6 + 2,1 3,6у - 1,5у = - 2 + 4,4 + 1,8
0,9х = 11,7 2,1у = 4,2
х = 11,7 : 0,9 у = 4,2 : 2,1
х = 13 у = 2
5) 2(0,6х + 1,85) - 0,7 = 1,3х 6) 0,2(5у - 2) = 0,3(2у - 1) - 0,9
1,2х + 3,7 - 0,7 = 1,3х 1у - 0,4 = 0,6у - 0,3 - 0,9
1,2х - 1,3х = - 3,7 + 0,7 1у - 0,6у = - 0,3 - 0,9 + 0,4
- 0,1х = - 3 0,4у = - 0,8
х = - 3 : (- 0,1) у = - 0,8 : 0,4
х = 30 у = - 2
б) =5х-10-6х-18-6х+27=-7х-1=7х+1
в) например, сделаем дробь и попробуем решить
=4/9*(2 целых 7/10 у + 2 целых 1/4 х) - 4 целых 2/10 * ( 5/7у - 5/10х) = 4/9*(27/10у+9/4х)-42/10*(5/7у-5/10х)=6/5у+х-3у+21/10=-1целых 4/5 у + 3 целых 1/10х можно и 1 целых 4/5у - 3 целых 1/10х или 1,8у-3,1х